Assessment of the 6th North American Duck Symposium (2013): â€œEcology and 512 Conservation of North American Waterfowlâ€ - Laborde, Lucien P.; Kaminski, Richard M.; Davis, J. Brian (Wildfowl, 2014)
Using web-based technology, we e-mailed a survey link to all 450 conferees of the 6thÂ North American Duck Symposium (NADS 6), â€œEcology and Conservation of NorthÂ American Waterfowlâ€ (ECNAW), seeking feedback from attendees in order to guideÂ the organisation of future waterfowl and other wildlife symposia. Twelve questionsÂ were posed to evaluate the 2013 all-waterfowl symposium and a further 18 questionsÂ to assist planning future similar meetings. A total of 284 responses (63%) wereÂ received; the feedback suggested that NADS 6 was well organised, that it presentedÂ relevant information and that it was valuable to conferees. Perceptions ofÂ respondents on the structure of NADS 6 (i.e. whether presentation on all waterfowlÂ should be included, or only on ducks) may not be representative of attendees ofÂ previous NADS meetings, as these focused on duck species. Nevertheless,Â respondents suggested that future symposia should continue on a 3-year rotation andÂ retain its 4-day format with four morning plenary sessions, concurrent afternoon oralÂ presentations and evening poster and mentee-mentor sessions. Respondents alsoÂ recommended a maximum of three concurrent afternoon sessions and indicated thatÂ future symposia might continue to embrace geese and swans as well as ducks. TheÂ results suggest a need for officials of NADS to determine future meeting frameworksÂ and venues. Web-based surveys provide a useful tool for conference evaluation andÂ can promote effective design and relevance of future meetings and related events.